Additively manufactured continuous carbon fiber-reinforced thermoplastic for topology optimized unmanned aerial vehicle structures - Goh, Guo Dong (2021)
The complete mechanical properties (tensile, compressive, and shear properties) of the additively manufactured (AM) continuous carbon fiber-reinforced thermoplastic (CFRTP) fabricated using extrusion-based AM technique were investigated and reported. The fracture modes of the AM CFRTP in various mechanical tests were studied and reported. Anisotropic mechanical properties were observed in all mechanical tests, with the fiber direction having the highest strengths and stiffnesses and the across-the-layer direction having the lowest strengths and stiffnesses. A proof of concept topology optimized unmanned aerial vehicle (UAV) landing gear was designed and fabricated using the mechanical properties obtained experimentally. Finite element analysis and compressive tests conducted show that the UAV landing gear structure fabricated using the AM CFRTP was able to survive the most extreme condition during operation.